The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1016/j.scitotenv.2020.141758
|View full text |Cite
|
Sign up to set email alerts
|

On-site analysis of COVID-19 on the surfaces in wards

Abstract: SARS-Cov-2 has erupted across the globe, and confirmed cases of COVID-19 pose a high infection risk. Infected patients typically receive their treatment in specific isolation wards, where they are confined for at least 14 days. The virus may contaminate any surface of the room, especially frequently touched surfaces. Therefore, surface contamination in wards should be monitored for disease control and hygiene purposes. Herein, surface contamination in the ward was detected on-site using an RNA extraction-free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 8 publications
2
19
0
Order By: Relevance
“…Moreover, we believe that examination room floor and corona wards floor are high-risk surfaces that contribute in spreading the virus and need to be targeted for extra cleaning. Wan et al (2020) attempted to identify the coronavirus at different surfaces of the hospital and revealed that a number of different samples taken from hospital surfaces such as handles, cupboards and light switches, door handle were positive for coronavirus ( Bloise et al, 2020 ), which was consistent with the results of the present study. Chia et al (2020a , b) also examined the identification of SARS-CoV-2 in hospital rooms of infected patients.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Moreover, we believe that examination room floor and corona wards floor are high-risk surfaces that contribute in spreading the virus and need to be targeted for extra cleaning. Wan et al (2020) attempted to identify the coronavirus at different surfaces of the hospital and revealed that a number of different samples taken from hospital surfaces such as handles, cupboards and light switches, door handle were positive for coronavirus ( Bloise et al, 2020 ), which was consistent with the results of the present study. Chia et al (2020a , b) also examined the identification of SARS-CoV-2 in hospital rooms of infected patients.…”
Section: Discussionsupporting
confidence: 89%
“…In fact, multiple surface contamination samples were from different wards before the daily cleaning and disinfection processes. These tests confirmed that 31 patients contaminated seven sites and among the collected sampled surfaces, the electrocardiogram fingertip presented a 72.7% positive rate, indicating that this surface should be considered as an important hygiene site, where more viruses can concentrate ( Wan et al, 2020 ). Moreover, SARS-CoV-2 RNA was detected on 30 (8.9%) of 336 environmental surfaces.…”
Section: Discussionmentioning
confidence: 57%
“…The inanimate environmental surfaces, especially frequently-touched surfaces, are one of the most important factors for virus transmission. Therefore, environmental surface contamination in different wards of the hospitals should be monitored to achieve hygiene goals and disease control ( Noorimotlagh et al, 2020 ; Moore et al, 2021 ; Wan et al, 2021 ). In this regard, in order to investigate the contaminated frequently-touched environmental surfaces, a total of 76 samples of SARS-CoV-2 were collected from different wards of a hospital designated for COVID-19 patients, while local officials had declared that the new variant of concern (VOC) 202012/01 (lineage B.1.1.7) had spread throughout Iran, especially Shoushtar city.…”
Section: Resultsmentioning
confidence: 99%
“…Studies of SARS-CoV-2 in toilets have so far been conducted in healthcare environments, which have higher frequency of, and more thorough, cleaning regimens than public toilets (Birgand et al, 2020;Cheng et al, 2020;Chia et al, 2020;D'Accolti et al, 2020;Jiang et al, 2020;Razzini et al, 2020;Santarpia et al, 2020;Shimabukuro et al, 2020;Wan et al, 2021;Ye et al, 2020). Despite this, faecal-derived aerosols in patients' toilets contained most of the detected SARS-CoV-2 in one hospital (Ding et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, fomite contamination offers a host of possible transmission pathways via hand touch surfaces after toilet flushing or direct touch from contaminated hands (e.g. toilet door handles: Cheng et al, 2020;Moore et al, 2021;sink: D'Accolti et al, 2020;Döhla et al, 2020;Gautret et al, 2020;Ge et al, 2021; taps, paper towel dispenser, hand dryers, bathroom door handles, etc., Lam et al, 2021;Verani et al, 2014;Wan et al, 2021; toilet flush: Ge et al, 2021; and toilet paper dispenser: Sassi et al, 2018). These may be contaminated with infective excreta, saliva and/or nasopharyngeal fluids unless sites are cleaned regularly (Chia et al, 2020;Ding et al, 2020;Ong et al, 2020).…”
Section: Bathroom Surfacesmentioning
confidence: 99%